The Controversy over the Authority of Āsim bin Bahdalah Al-Kufi in Qira’at Studies and Hadith Studies during the Abbasid Dynasty - Muhammad Rikza Muqtada (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
This article explores the comparative authority of Āsim b. Bahdalah al-Kufi in the realms of Qur’anic recitation and hadith studies. Āsim, who lived in the second century AH (128 A.H.), held a significant position in the field of qira’at, boasting a substantial following, including in Indonesia. His narration of the qira’at was widely recognized for its high degree of authenticity and reliability. However, when it came to the domain of hadith studies, his authority faced negative evaluations (majruh) from critics in this field. This study adopts a critical historical approach to scrutinize the disparities in Āsim b. Bahdalah’s authority between Qur’anic qira’at and Hadith studies. The findings of this investigation reveal that these discrepancies in authority were closely linked to political factors associated with the ‘Abbasid dynasty. Abu ‘Ali Muhammad b. ‘Ali b. Muqlah al-Shirazi, a prominent Minister in Baghdad during the Abbasid era, played a pivotal role in shaping the views of Ibn Mujahid and influencing the content of his work. Ibn Mujahid opted to document the name of Āsim b. Bahdalah over Abu Muhammad Ya’qub b. Ishaq al-Hadrami al-Basri, who was deemed disloyal to the Abbasid rulers. The political pressure exerted by the Abbasid rulers appears to have played a crucial role in his decision-making process. In fact, the Abbasid rulers went to great lengths, even compelling scholars who disagreed with Ibn Mujahid’s views to retract their positions and issue apologies for their dissent. Some scholars were subjected to imprisonment as a consequence of their refusal to align with the official viewpoint. This comparison underscores how politics had the capacity to wield substantial influence over the assessment of intellectual authority across various fields of knowledge in historical contexts.